Optical and structural investigation of Cu2ZnSnS4 based solar cells (Phys. Status Solidi B 11/2016). Issue 11 (8th November 2016) - Teixeira, Jennifer P.; Salomé, Pedro M. P.; Sousa, Marta G.; Fernandes, Paulo A.; Sadewasser, Sascha; da Cunha, António F.; Leitão, Joaquim P.
Abstract : The low‐cost and earth‐abundant compound Cu2 ZnSn(S, Se)4 (CZTSSe) is emerging as a promising absorber layer in thin‐film photovoltaics technology. To improve the power conversion efficiency in CZTSSe‐based solar cells, different sulphurization methods have been investigated. An important issue is the influence of the growth conditions on the electronic structure and charge carriers dynamics. Teixeira et al. (pp.2129–2135 ) observed that the grain size is dependent on the sulphurization method, being larger for the sulphurization in S flux in comparison with the use of a graphite box. In the first case, the electronic structure is influenced by electrostatic fluctuating potentials, which is observed in photoluminescence (PL) measurements through a broad and asymmetric band and a large blueshift with the increase of the excitation power. For the sulphurization in a graphite box, the PL has a much lower intensity and is dominated by the emission from a CdS buffer layer in the solar cell structure. The authors propose that PL can be used as an evaluation experimental technique in order to decide if the absorber should be processed into a full solar cell or not.